Keawetan Alami Kayu Eboni (Diospyros celebica) Bagian Dalam dan Luar Terhadap Serangan Rayap Kayu Kering (Cryptotermes cynocephalus) - Nisrina Putri Hanifah; Agung Nugrawan Kutana; Silvia Uthari Nuzaverra Mayang Mangurai (Universitas Satya Terra Bhinneka, 2025)
The natural durability of wood is determined by the content of extractive substances that are toxic to destructive organisms such as fungsi and termites. Ebony wood, known for its strength and economic value, has a high extractive content that makes it resistant to drywood termite attack. This study examines the ability of ebony wood to resist termite attack, offering a natural solution to reduce wood damage in Indonesia. Specific research on the matural durability of ebony against drywood termite attack, whisch has not been widely studied in depth. Differences in durability between the inside and outside of the wood, as well as the effectvness of ebony wood against termites, which offers a natural alternative for wood protection in tropical regions such as Indonesia. This study used ebony wood (inside and outside) and pine wood as a control to test its natural durability against drywood termites. The wood durability test was conducted using the standard method of SNI 01-7207-2014, with 12 weeks of observation of wood damage and termite mortality. This study evaluated the physical properties and durability of ebony (inside and outside) and pine wood against drywood termites. Moisture content measurements showed that pine wood has a higher MC than ebony wood, with outer ebony wood slightly higher than inside wood. The density and specific gravity of ebony wood are higher than pine wood, which is related to its extractive substance content. Durability test showed ebony wood, especially the inside part, had lower weightloss and termite mortality than pine wood, indicating higher durability due to the content of toxic extractives.